PENGUJIAN ANOMALI PASAR : DAY OF THE WEEK EFFECT PADA SAHAM LQ-45 DI BURSA EFEK INDONESIA - Trisnadi, Margareta Maria; Panji Sedana, Ida Bagus (E-Jurnal Manajemen, 2016)
One of market anomaly that againsts the concept of efficient market is Day of The Week Effect, which is an anomaly where there are differences between stock returns on trading day. The purpose of this study is to determine the existence of the anomaly on LQ-45 index on Indonesia Stock Exchange. The test was conducted using multiple linear regression with dummy variables and partial test. Based on test results, Tuesday had a negative effect, while Wednesday and Friday had positive effects, but all insignificant. Only Thursday that provides a significantly positive effect on stock returns. From these results the phenomenon of Day of the Week Effect was found, with the highest average returns on Thursday, commonly known as Thursday Effect. Investors need to pay attention to the existence of Day of the Week Effect as part of the plan and investment strategy to optimize return.
Keywords: efficient market; day of the week effect; stocks return